Coordinating aid for regional cooperation projects: The experience of Central Asia - Richard Pomfret (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
For the Central Asian countries the dissolution of the Soviet Union led to economic disintegration as old coordination mechanisms disappeared and new national borders appeared. This paper analyses why it has been difficult to coordinate aid for regional cooperation projects (e.g., on the Aral Sea or trade facilitation) whose economic benefits appear positive. Bilateral aid flows to Central Asia have been dominated by geopolitical rather than economic considerations, and have been at best narrowly national in focus and at worst regionally divisive. Regional organizations composed of Central Asian countries and various neighbours have also competed rather than cooperated, so that the most plausible source of coordinated aid for regional cooperation projects is the multilateral agencies. A key role for aid donors is to provide technical assistance in analysing and explaining benefits, and how these affect various interests. Initial advantages which multilateral agencies had as impartial providers of technical advice were undermined in 1992-93 when the IMF's strong position in favour of retaining the ruble turned out to be mistaken advice. In the 1990s aid directed to the Aral Sea problem produced few benefits because, despite the magnitude of the gross benefits from reversing the desiccation, littoral countries see differential benefits and costs; pure win-win situations are more likely from regional cooperation in trade facilitation. Subsequently the multilateral agencies have had a better focus, sharing priorities in the destination of aid and agreeing on a functional division of labour, but this has not yet translated into effective assistance for regional cooperation. – aid ; Central Asia ; trade
Keywords: F35; F15; O18; R12; 330; Internationale Wirtschaftshilfe; Entwicklungskooperation; Zentralasien